THE INITIAL TREATMENT RESULTS OF 6 PATIENTS WITH NON-SMALL CELL LUNG CANCER WITH EGFR AND ALK CONCURRENT MUTATIONS, AT THE CENTRAL LUNG HOSPITAL - Le Tu Linh,; Nguyen Viet Nhung,; Nguyen Hoang Anh,; Le Ngoc Minh Thu,; Hoang Huy Anh,; Nguyen Dieu My,; Nguyen Thi Trang, (Tạp chí Y học Quân sự, 2024)
Purpose: Evaluate the initial treatment results of non-small cell lung cancer with EGFR and ALK concurrent mutations. Subjects and methods: A prospective study, non-controlled description, and longitudinal follow-up of 6 patients with stage IIIB-IV non-small cell lung cancer, with EGFR and ALK concurrent mutations, at the National Lung Hospital, from January 2022 to July 2023. Results: The average age of patients was 65.5 years, the male/female gender ratio was 5/1, and the proportion of patients who smoked was 83.3%. Patients were mainly admitted to the hospital due to symptoms of cough (100%), chest pain (50.0%), and dyspnea (33.3%); the majority of patients with stage IV cancer (83.3%); all patients had adenocarcinoma (100%). The average disease-free survival time was 11.36 months. The common unwanted effects were mainly skin rash (83.3%) and diarrhea (66.7%). Elevated liver enzymes and renal failure occurred in the group of patients using a combination of EGFR-TKIs and ALK-TKIs and were the reasons for discontinuation of ALK-TKIs.